2021
DOI: 10.1093/emph/eoab010
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary mismatch narrative to improve lifestyle medicine: a patient education hypothesis

Abstract: An evolutionary perspective provides a unifying explanation for the modifiable risk factors and lifestyle-based interventions for the leading causes of morbidity and mortality globally. Non-communicable diseases develop from an evolutionary mismatch between the prior environment and modern patterns of behavior; however, it is unclear whether an evolutionary mismatch narrative could promote positive behavior change in patients. We hypothesize that educating patients about evolutionary mismatch could augment eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Consistent with previous studies on general cardiac patients (Basile et al, 2021), the educational intervention in this study enhanced the adoption and efficacy of health-promoting behaviors in the participants. Sogaro et al (2010) previously reported improved social functioning in cardiac patients with type D personalities after cardiac rehabilitation, and a study in South Korea found significant improvement in social functioning in female cardiac patients with type D personality after a psycho-behavioral intervention (Hur et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with previous studies on general cardiac patients (Basile et al, 2021), the educational intervention in this study enhanced the adoption and efficacy of health-promoting behaviors in the participants. Sogaro et al (2010) previously reported improved social functioning in cardiac patients with type D personalities after cardiac rehabilitation, and a study in South Korea found significant improvement in social functioning in female cardiac patients with type D personality after a psycho-behavioral intervention (Hur et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Our research observed a rapid regain of visceral fat in the participants once caloric restriction and high physical activity ceased. Therefore, it is crucial to maintain habits more aligned with our evolutionary heritage, as opposed to those of modern civilization, which promote sedentarism and the consumption of hypercaloric foods with little nutritional value [39]. Regarding skeletal muscle mass, we found a decrease in both participants when comparing results from the initial analysis to those at the end of the fourth day.…”
Section: Resultsmentioning
confidence: 74%
“…On the contrary, today we live in ecological niches with the continuous availability of food, but genes continue to be set to obtain as much energy as possible within the perspective of a potential paucity of nutrients. This behavior implies a shortening of life, resulting from the fact that the overproduction of energy in the cells takes place at the level of the mitochondria to obtain the primary source as ATP, but this process has a cost in terms of oxidative stress and cellular damage [50][51][52][53][54]. At the physiological level ROS act as redox messengers, while excesses damage cells [55].…”
Section: Gerontogenesmentioning
confidence: 99%